Ethical Dimension of Cult in the Book of Isaiah. By Bohdan Hrobon - Tiemeyer, Lena-Sofia (The journal of theological studies, 2012)
This monograph, the author's D.Phil. thesis from the University of Oxford, examines the ethical aspects of Israel's cult, expressed by three select texts in the book of Isaiah. In contrast to previous scholars who regard the relationship between priests and prophets as either antithetical or complementary, Hrobon argues that priests and prophets of ancient Israel shared the same theology. The main purpose of the cult was to maintain God's presence among his people. Because God is holy, his presence requires purity. Grave sins, such as murder, idolatry, adultery, etc., cause defilement and thus bring about impurity, to both the people and the land, which no ritual can render pure. When impure people in an impure land performed the standard cult of Yhwh, that cult became an abomination.